Alternative Funding Practices of Sailaja Acharya Memorial Polytechnic, Morang, Nepal - Koirala, Amit (International Journal of Social Sciences and Management, 2015)
This study “Alternative funding practices of Sailaja Acharya Memorial Polytechnic (SAMP) explores the approach in practice in the institution even exploring its sustainability and replicability. In so doing the evidences clearly indicate the challenges with the existing practices in the institutions even though the institution has made reliable strategic interventions to overcome them. There are no valid grounds for applying such alternative financing model for its replication in Nepalese context. For carrying out qualitative research, researcher employed case study research design. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12434 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 184-187